ANALYSIS OF PURCHASING ACCOUNTING INFORMATION SYSTEM FOR INVENTORY PROCUREMENT EFFICIENCY AT CV. EKATUNGGAL TIMUR MANADO - Archelia Avril Margareth Dalisang; Dominikus Andreo Maryadi; Sintia Nurani Korompis (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the implementation of a purchasing accounting information system to improve the efficiency of the inventory procurement process. This study uses a qualitative descriptive approach with CV. Ekatunggal Timur Manado as the object. Data was obtained through observation, semi-structured interviews with the purchasing, warehouse, and accounting departments. Data were then analyzed using a descriptive approach, internal control checklist, and efficiency indicators. The results show that the system has been running with the support of ERP and fairly structured procedures. However, the system is not optimal due to the lack of clear separation of duties, lack of system integration, and communication constraints between divisions. In addition, delays from suppliers also impact inventory imbalances such as overstock and stockouts. The results of this study indicate that the effectiveness of the purchasing accounting information system is greatly influenced by the quality of internal control and system integration. Therefore, the company needs to strengthen the separation of duties, improve ERP integration, and improve coordination between divisions to improve procurement efficiency. This study offers a more focused analysis of the relationship between the purchasing accounting information system, internal control, and procurement efficiency in the context of a distribution company.